A bioethical analysis of the quantified relationship - Pillay, Priyanka Calyn (My University, 2022)
Objective Quantified Relationship Technologies refer to technologies that track and gamify components of interpersonal, romantic relationships. The tracking and gamifying occur through three interrelated phenomena: Intimate tracking, Intimate gamification, and Intimate surveillance. As intimate relationships are regarded as an intrinsic good and offer a wide range of benefits to human health and well-being, applying these technologies in this sphere of human life has ethical implications. This research report provides a bioethical assessment of the merit of three objections to the Quantified Relationship phenomenon. Methodology This research report uses Normative methods to assess the merit of three objections present in the Quantified Relationship literature; the instrumental-intrinsic value problem objection, the informal-reciprocation objection, and the privacy objection. The report begins by describing the Quantified Relationship phenomenon. I then outline and critically analyse each of the three objections in turn. Finally, within the context described, this research report argues and defends the position that the Quantified Relationship phenomenon raises valid ethical concerns regarding the intrinsic and instrumental goods they produce, the relationship models used and the privacy risks for intimate partners. Conclusions In this bioethical analysis, I find that objections to the Quantified Relationship phenomena express valid concerns. However, the merit of these objections is such that they are not terminal arguments for the Quantified Relationship phenomenon. Instead, the concerns raised can guide us on ethically deploying Quantified Relationship technologies in intimate relationships.
A Research Report submitted in partial fulfilment of the requirements for the degree of Master of Science in Medicine (Bioethics and Health Law) to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2022